PUBLIC PARTICIPATION AND ERADICATION OF POVERTY AND HUNGER IN ENUGU STATE, NIGERIA. (Journal of the Management Sciences, 2023)
Poverty and hunger have been seen as major problems in Enugu state despite the existence of numerous poverty alleviation programmes such as National Poverty Eradication Programme (NAPEP), Women for Women International Programme, Visit Every Community (VEC) Project initiated by former governor Sullivan I Chime in 2013, Every Community 10 million naira project initiated by the immediate past governor Ifeanyi Lawrence Ugwuanyi, N-Power, etc. Therefore, for the purpose of this study, it focuses on Nusska Local Government Area (LGA). The study is poised to ascertain the effect of public participation on the eradication of poverty and hunger in Nsukka Local Government Area (LGA). The study adopted participatory approach as its theoretical framework. The research applied a cross – sectional research design with an in-dept interview as an instrument of research data collection. Total of twenty eight respondents at the ratio of two respondents each from the fourteen towns that made up Nsukka LGA were purposively selected as the sample size. The collected data were later analysised thematically. And the study found out that poverty is ravaging Nsukka LGA because of non inclusion of the public on decision making. And that project providers usually carry out project of their choice in any community they wish without seeking to know the felt needs of the community. Also corruption, absent of effective legislation and lack of proper monitoring were discovered as cause of poverty and hunger in Nsukka LGA. The study further recommends that government and project providers should prioritise public participation in decision making, there should be effective legislation that will be checking mating the excesses of both project providers and the public. Finally, that project should be provided in line with the felt needs of the people.
Keywords: Public participation; Poverty; Hunger; Democracy